(untitled) (Journal of the College of Basic Education, 2022)
The problem of the current research is that it is an attempt to answer whether the more intelligent individuals are more able to perceive time and thus estimate its importance for them and for others. ?At a time when the local community is characterized by disregard for time and indifference to the importance that time represents to individuals, society and the progress of nations, and its connection to issues of respect for the human right to control his time and the freedom to dispose of it and respect his privacy, (Hassan, 2006, p. It is one of the elements of their personality and one of their methods of controlling their lives in terms of arranging priorities, planning for the future, and realizing the repulsive elements during the course of life in the past.